In vitro acaricidal activity of Azadirachta indica and Phytolacca dodecandra leaves and their combination on Rhipicephalus (boophilus) decoloratus - Kiconco, Catherine; Ajayi, Clement Olusoji; Mugisha, Kamatenesi Maud; Engeu, Ogwang Patrick (Journal of Medicinal Herbs and Ethnomedicine, 2022)
Rhipicephalus (boophilus) decoloratus (ticks) are causing great economic loss among the cattle rearers from cattle mortalities and costs during the treatments. Synthetic acaricides have been used for a long time in the management of ticks, however chemical resistance from multiple uses of acaricides as well as contamination of dairy products from these acaricides has caused the urgent need for alternative herbal drugs. This study evaluated in vitro activity of the combination of Phytolacca dodecandra L’Her and Azardirachta indica A. Juss against R. (boophilus) decoloratus (ticks) with a view to developing active, less toxic and non-resistant acaricides. P. dodecandra and A. indica were collected, dried after authentication, pulverised mechanically and extracted with cold water. Ticks were treated with the herbal extracts singly and then in combination with concentrations ranging between 50-100mg/mL of distilled water. The anti-tick activity of P. dodecandra and A. indica was compared with Duodip and Ametix which are synthetic acaricides currently being used by farmers in Western Uganda. Results showed that P. dodecandra extract gave the highest mortality of ticks (65%) compared with A. indica (50%), Duodip (40%) and Ametix (5%) within a period of 12– 48 hours after exposure to the treatment. A combination of the two medicinal plant extracts (50%) did not show any significant difference in tick mortality compared to P. dodecandra. Phytolacca dodecandra has potential benefits thus may be used to obtain a natural eco-friendly acaricide for the management of ticks, however, a combination of the two medicinal herbal extracts has little synergistic effect compared to when P. dodecandra is used alone.